Just enough data science and machine learning essential tools and techniques - Levene, Mark; Harris, Martyn (Hoboken, NJ Addison Wesley, 2024)
"An accessible introduction to applied data science and machine learning, with minimal math and code required to master the foundational and technical aspects of data science. In Just Enough Data Science and Machine Learning, authors Mark Levene and Martyn Harris present a comprehensive and accessible introduction to data science. It allows the readers to develop an intuition behind the methods adopted in both data science and machine learning, which is the algorithmic component of data science involving the discovery of patterns from input data. This book looks at data science from an applied perspective, where emphasis is placed on the algorithmic aspects of data science and on the fundamental statistical concepts necessary to understand the subject"--Provided by publisher.
What is data science? -- Basic statistics -- Types of data -- Machine learning tools -- Data science topics -- Selected additional topics -- Further reading.
Includes bibliographical references and index.
Keywords: Electronic data processing; Computer science; Python (Computer program language); Computer programming; Machine learning